Perfil epidemiológico dos acidentes ocupacionais por exposição a material biológico da micro-região de Votuporanga, período de 2001 a 2005 - Dias, Maria Aparecida do Carmo (2007)
The present study aimed characterizing the aforesaid accidents notified in the reference services in Votuporanga’s micro-region, in the period from 2001 to 2005, through the identification of the happenings according to the injured professional category, exposure type, exposure place, biological material type, and the causer agent; Determining the involved serological state and the adopted behavior; Characterizing the injured serological state follow up and the cases evolution. The data were collected from the notification cards from Votuporanga’s Epidemiological Vigilance Service and from the DIR XXII São José do Rio Preto. From the 273 informed accidents, 214 (78,4%) occurred with the female sex and 190 (69,6%) in the age between 20 and 40 years. The town that most informed accidents was Votuporanga with 243 (89,0%) cases. Most of the accidents occurred in the year of 2002 (23,8%), then 2005 (22,7%), 2003 (19,4%), 2004 (18,7%) and 2001 (15,4%). The hospital was the place where most of the accidents occurred (65,6 %). The nursing auxiliary was the professional category most exposed (48,4%), and 99,6% of the injured received medical attendance within 72 hours. The most frequent exposure type was the percutaneous, in 237 (86,8%) cases, and the highest contact made by biological material was reached by the blood (98,5%). The needle with lumen was the device that most provoked accidents (72,1%). From the injured, 239 (87,5%) had the HBV vaccine and of these, 67,0% did not have anti-HBs. The injured serological state evaluation detected one HIV positive, one HBV positive and four HCV positive. From the 229 (83,9%) anti-HIV serology results of known sourcepatients, 11 (4,8%) were positive. From the total of notifications, 44 (16,1%) were HIV unknown source. From the referred serological evaluation related to HBV, 215 (78,8 %) were known source, of which, five (2,3%) were positive, of the injured was not followed up for six months. From the total notification number, 58 (21,2%) were unknown source and 14 injured were not followed up. For HCV, it was detected 215 (78, 8%) known source-patients serology, of which, seven (3.3%) were positive (two injured were not followed up), from the total notifications 58 (21,2%) were unknown source of which 15 injured were not followed up. There were ARVs indications in only 20 (7,3%) of the notifications, and two injured did not have a serological follow up. The 35 accidents with unknown source were not advised to use the ARVs and 14 (40,0%) of these also were not followed up. The type of discharge related to HIV, 218 (79,8%) were negative source, 39 (14,3%) sorus conversion absence and 16 (5,9%) abandonments. Such preliminary diagnosis seems indicating the necessity of elaborating a local intervention plan, its implementation may count on the community allowance, which is, unquestionably, co-responsible for the changes proposals.